A FUNDAMENTAL KNOWLEDGE FOR ACCELERATING CAREER IN FINANCIAL INDUSTRY - Made Irma Lestari (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
In order to educate the life of the nation, this community service activity takes the theme of career development in the financial industry. The financial industry in Indonesia shows a large contribution in providing employment opportunities. The financial services industry sector is a place providing a great opportunity to millennial leaders of the country's economic industry which is certainly a wetland for them to gain as much experience as possible to prepare for accelerating career. This community service activity was packaged in the form of a webinar with the aim of providing fundamental knowledge related to the financial services industry that participants must know. This webinar provided the understanding of the types of services and government institutions that have regulatory authority. Presentations related to the development of the financial industry and the role of product manager position topics discussed in the next session and continued with anexplanation of the transition from a learner to a professional in the financial industry.